Loading ...
Sorry, an error occurred while loading the content.

25183Multiplying Primes and Numbers in General

Expand Messages
  • Kermit Rose
    Jun 19, 2013
    • 0 Attachment
      Yes.

      I understand your concept.

      I have worked with those equations also.

      (6 a -1)(6b - 1) = (36 a b - 6 a - 6 b + 1) = 6 ( 6 ab - a - b) + 1

      (6 a - 1) (6 b + 1) = 36 a b + 6 a - 6 b - 1 = 6 ( 6 a b + a - b) - 1

      (6 a + 1) (6 b - 1) = 36 a b - 6 a + 6 b - 1 = 6 ( 6 a b - a + b) - 1

      (6 a + 1) (6 b + 1) = 36 a b + 6 a + 6 b + 1 = 6 ( 6 a b + a + b) + 1


      Kermit
    • Show all 7 messages in this topic